International Cooperation in Hydrography and Modern Techniques in Hydrographic Surveying - Fraser, F. L. (The International Hydrographic Review, 2015)
There is nothing more timely and urgent than the need for promoting international cooperation in hydrography and for considering the development, uses and need for employing modern techniques in hydrographic surveying. The International Hydrographic Organization has always given particular attention to international cooperation in hydrography in the widest sense. The role played by IHO and the manner in which FIG could possibly assist IHO in promoting international cooperation in hydrography are explained in the address. The period since World War II has probably seen more changes than any similar period in the history of the world. The impact of these changes has been such that charts of many of the world’s economically strategic waterways were made obsolete and inadequate, while maritime trade developed in many new areas where existing charts were found hopelessly inadequate. While regional or sub-regional cooperative efforts are a means by which hydrographic surveying and nautical charting programmes could lead to more adequate and up-to-date charts, the problems of developing countries that have little or no hydrographic capability need very special attention. As in other fields, hydrographic surveying has witnessed spectacular technological advances in recent years. This technology and future developments must be exploited to the full and their benefits must not be limited to the few. The establishment and strengthening of hydrographic capabilities of developing countries through international cooperation are vital to the attainment of the IHO’s objective of providing up-to-date charts, based on internationally accepted standards, which in turn would benefit the international maritime community in an increasingly interdependent world.